1994
DOI: 10.1209/0295-5075/25/6/012
|View full text |Cite
|
Sign up to set email alerts
|

Angular Dependence of Giant Magnetoresistance in Magnetic Multilayered Structures

Abstract: We present an analytical quantum-statistical theory of the angular variation of the giant magnetoresistance (GMR) in magnetic multilayers (current flowing in the plane of the layers) which takes into account both spin-dependent scattering of conduction electrons and spin-dependent potential barriers between successive layers. We show that the widely accepted linear variation of the GMR with the cosine of the angle between the magnetizations in the successive ferromagnetic layers is valid when the GMR originate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 14 publications
(10 reference statements)
1
23
0
1
Order By: Relevance
“…These results show that there is a simple cos ϕ dependence in the limit when the mean free path of the electrons is large compared to the thickness of the layers [1]. When the role of the variation of the lattice potential from layer to layer is included in the free electron models, one finds deviations from the cos ϕ dependence [2], but no clear trends have been established. For example, Vedyayev et al (see Ref.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…These results show that there is a simple cos ϕ dependence in the limit when the mean free path of the electrons is large compared to the thickness of the layers [1]. When the role of the variation of the lattice potential from layer to layer is included in the free electron models, one finds deviations from the cos ϕ dependence [2], but no clear trends have been established. For example, Vedyayev et al (see Ref.…”
Section: Introductionmentioning
confidence: 90%
“…For example, Vedyayev et al (see Ref. [2]) discussed the general case with both spin-dependent scattering and potential barriers between successive layers for a spin valve structure, and showed that when the spin-dependent lattice potential is included, the resistivity is no longer a linear function of cos ϕ. For current in the plane of the layers (CIP), experiments have found for the most part, the simple cos ϕ behavior [3]; however for current perpendicular to the plane of the layers (CPP), significant deviations have been established [4].…”
Section: Introductionmentioning
confidence: 99%
“…18 The nonlinearities were associated with asymmetrical features of 024421-3 the structure, such as different FM layers, spin-dependent potentials at interfaces, and device boundaries. 10,19 Our CIP geometry results show directly that the linear behavior of MR with cos φ is valid in the whole angular range. This is direct experimental evidence that the magnetoresistive response depends on the intrinsic anisotropy of a multilayer structure through its angular-dependent magnetization reversal processes, and, ultimately, that it relies on the relative orientation of the FM layers.…”
Section: Mr (%)mentioning
confidence: 51%
“…В общем случае неколлинеарной намагниченности функция Грина представляет собой матрицу размером 2 × 2 [5]. При построении функции Грина многослойной системы приходится решать ряд задач, обусловленных геометрией исследуемой си-стемы: сшивка на границах между слоями, наложение граничных условий.…”
Section: Introductionunclassified